Optimum Nitrogen and Phosphorus Combination Improved Yield and Nutrient Use Efficiency of Sorghum in Saline Soil - Xiaoqian Guo; Qidi Wu; Luqi Wang; Guisheng Zhou; Guanglong Zhu; Mohamed Suliman Eltyb Suliman; Nimir Eltyb Ahmed Nimir (Plants)
Two-year experiments were conducted to assess the responses of yield and nutrient use efficiency of sorghum to nitrogen and phosphorus under saline soils. Three nitrogen rates (0, 180, and 360 N kg ha−1) and three phosphorus rates (0, 60, and 120 P2O5 kg ha−1) were used in this study. Our results showed that nitrogen and phosphorus supply increased SPAD (leaf greenness, 5.0–29.1%), NSC (non-structural carbohydrates, 14.0–41.2%), nutrient accumulation (nitrogen: 14.1–50.0%, phosphorus: 11.8–41.5%, potassium: 13.7–28.2%), biomass (fresh: 10.8–29.3%, dry: 5.0–22.8%), yield (16.6–30.7%), and harvest index (2.0–9.8%) of sorghum at the maturity stage grown in saline soils but significantly decreased nutrient use efficiency. Combined application showed better performance on these attributes than sole nitrogen and sole phosphorus. The highest seed yield (5919 kg ha−1) was recorded at 180 N kg ha−1 and 60 P2O5 kg ha−1 treatment, while the largest value of dry biomass (18,401 kg ha−1) was obtained at 360 N kg ha−1 and 120 P2O5 kg ha−1 treatment. The Pearson analysis showed that seed yield had the highest correlation with aerial potassium accumulation, while dry biomass had the highest correlation with NSC as well as aerial nitrogen accumulation. A treatment of 180 N kg ha−1 and 60 P2O5 kg ha−1 was recommended to be used in sorghum production in saline soils based on harvest index and nutrient use efficiency.